Shorter Leukocyte Telomere Length in Relation to Presumed Nonalcoholic Fatty Liver Disease in Mexican-American Men in NHANES 1999–2002 - Janet M. Wojcicki; David Rehkopf; Elissa Epel; Philip Rosenthal (International Journal of Hepatology)
Leukocyte telomere length is shorter in response to chronic disease processes associated with inflammation such as diabetes mellitus and coronary artery disease. Data from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2002 was used to explore the relationship between leukocyte telomere length and presumed NAFLD, as indicated by elevated serum alanine aminotransferase (ALT) levels, obesity, or abdominal obesity. Logistic regression models were used to evaluate the relationship between telomere length and presumed markers of NAFLD adjusting for possible confounders. There was no relationship between elevated ALT levels, abdominal obesity, or obesity and telomere length in adjusted models in NHANES (OR 1.13, 95% CI 0.48–2.65; OR 1.17, 95% CI 0.52–2.62, resp.). Mexican-American men had shorter telomere length in relation to presumed NAFLD (OR 0.07, 95% CI 0.006–0.79) and using different indicators of NAFLD (OR 0.012, 95% CI 0.0006–0.24). Mexican origin with presumed NAFLD had shorter telomere length than men in other population groups. Longitudinal studies are necessary to evaluate the role of telomere length as a potential predictor to assess pathogenesis of NALFD in Mexicans.